Antistatic TPU particle and preparation method thereof

By introducing fillers such as carbon nanotubes, reduced graphene oxide and modified fibers into TPU materials, the conductive network and mechanical complexing are formed, which solves the problem of insufficient anti-static and tensile properties of TPU materials, and significantly improves its anti-static and Tensile performance, suitable for high-end applications.

CN119242022AInactive Publication Date: 2025-01-03DECHUANG THERMOPLASTIC POLYURETHANE (DONGGUAN) CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411601394.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-01-03
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Traditional TPU materials have insufficient antistatic performance and limited tensile performance during use, making it difficult to meet the application needs of high-end fields, especially in electronics, medical and automobiles.

Method used

Antistatic TPU particles are prepared by ultrasonic cleaning, temperature-controlled drying and melt blending to form conductive network structure and mechanical fillers. Combination, enhances electrical conductivity and mechanical properties.

Benefits of technology

It significantly improves the anti-static effect and tensile performance of TPU particles, reduces volume resistivity and surface resistivity, and enhances the stability and strength of the material, meeting the safety and performance requirements of high-end applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005128412690000011
    Figure BDA0005128412690000011
  • Figure BDA0005128412690000021
    Figure BDA0005128412690000021
  • Figure BDA0005128412690000051
    Figure BDA0005128412690000051
Patent Text Reader

Abstract

The invention relates to an antistatic TPU particle and a preparation method thereof, and belongs to the technical field of TPU, the TPU particle comprises the following raw materials: polyester type thermoplastic polyurethane elastomer, carbon nanotube, reduced graphene oxide, modified silicon dioxide, modified wood fiber, didodecane dimethyl ammonium bromide, octyl tributyl phosphonium bis (trifluoromethanesulfonyl) imine salt, melamine and N, N-dimethylformamide. And N, N-dimethylformamide is used as a solvent. According to the invention, carbon nanotubes and reduced graphene oxide are selected as antistatic fillers, didodecane dimethyl ammonium bromide is added to modify the antistatic fillers, and octyl tributyl phosphonium bis (trifluoromethanesulfonyl) imine salt is used to make up a part of conductive network defects of the antistatic fillers, so that TPU particles with an antistatic effect are prepared; besides, modified silicon dioxide and modified wood fibers are compounded on the basis of the carbon nanotubes, and melamine is added at the same time, so that the prepared TPU particles have excellent tensile property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of TPU, and in particular relates to antistatic TPU particles and a preparation method thereof. Background Art

[0002] Thermoplastic polyurethane elastomer (TPU) has good elasticity, wear resistance, low temperature resistance and oil resistance. It is often used in many fields such as footwear, automobiles, electronics, sports, and medical treatment. Its molding process can be processed by injection molding machines or extruders. The production process is clean, hygienic, environmentally friendly and pollution-free. However, traditional TPU materials often face the problems of insufficient antistatic performance and limited mechanical properties during use, which leads to the accumulation of static electricity in daily use or production and processing, and it is difficult to meet the anti-static requirements of various industries. Insufficient antistatic performance may lead to static electricity accumulation, causing safety hazards such as electric shock and fire, especially in sensitive fields such as electronics, medical treatment and chemical industry; in addition, for some high-strength automotive parts and sports equipment application scenarios, the tensile properties of existing commercially available TPU materials also need to be further improved.

[0003] Therefore, the development of a TPU particle with both antistatic and high tensile strength and a preparation method thereof has extremely important practical significance and can provide strong support for the application of TPU in more high-end fields. Summary of the invention

[0004] The purpose of the present invention is to provide an antistatic TPU particle and a preparation method thereof, which solves the problem of poor antistatic and tensile properties of TPU particles in the prior art.

[0005] The purpose of the present invention can be achieved by the following technical solutions:

[0006] An antistatic TPU particle, the TPU particle specifically comprises the following raw materials in parts by weight:

[0007]

[0008]

[0009] As a preferred technical solution of the present invention, the TPU particles also include N,N-dimethylformamide.

[0010] Furthermore, the N,N-dimethylformamide is 200-300 parts by weight.

[0011] Carbon nanotubes are a type of hollow tubular structure material with a large aspect ratio, high hardness, and good electrical conductivity. They can effectively improve the electrical conductivity and mechanical properties of materials at the same time.

[0012] Reduced graphene oxide refers to the product obtained by reducing graphene oxide. Its surface defect sites are less than those of graphene oxide. It is closer to single-layer graphene in structure and properties and has excellent conductivity.

[0013] Silica nanoparticles have high hardness and high surface reactivity. When subjected to external forces, the interface interaction between the silica nanoparticles and the matrix is ​​strong, which can effectively transfer stress and reduce damage to the matrix material.

[0014] Wood fiber has excellent flexibility, high specific strength, high modulus and recyclability. It can effectively enhance the support and durability of the system, and improve the stability and strength of the system.

[0015] As a preferred technical solution of the present invention, the polyester thermoplastic polyurethane elastomer, brand: WHT-1185, purchased from Wanhua Chemical Group Co., Ltd.; the carbon nanotubes have a radial size of nanometers and an axial size of micrometers, CAS number: 308068-56-6, purchased from Shanghai Liantian Materials Technology Co., Ltd.; the reduced graphene oxide, number of layers: single layer, sheet diameter: 1-5μm, item number: R487602, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the modified silica is nano silica modified with γ-aminopropyltriethoxysilane, purchased from Xi'an Qiyue Biotechnology Co., Ltd.; the octyltributylphosphonium bis(trifluoromethanesulfonyl)imide salt, CAS number: 934215-88-0, purchased from Changsha Binghang New Materials Co., Ltd.

[0016] As a preferred technical solution of the present invention, the preparation method of the modified wood fiber includes the following steps: ultrasonically cleaning the wood fiber in N,N-dimethylformamide, washing, and temperature-controlled drying, adding Tris hydrochloride solution to the dried wood fiber for ultrasonic dispersion, then adding dopamine hydrochloride, adjusting the pH, ultrasonically, standing, taking out the wood fiber, washing, and temperature-controlled vacuum drying to obtain the modified wood fiber.

[0017] Furthermore, the wood fiber has a diameter of 8-12 μm.

[0018] Furthermore, the amount of N,N-dimethylformamide added is just enough to cover the wood fiber; the amount ratio of the dried wood fiber, Tris hydrochloride solution and dopamine hydrochloride is 3-4g:220-240mL:0.5-0.7g.

[0019] Furthermore, the ultrasonic cleaning time is 2-2.5h; the washing is performed with deionized water for 3-5 times; the temperature of the temperature-controlled drying is 95-100°C and the time is 10-12h; the concentration of the Tris hydrochloride solution is 10mmo l / L; the ultrasonic dispersion time is 15-20min; the pH is adjusted by using 0.1mol / L sodium hydroxide solution to adjust the pH to 8.5; the ultrasonic and standing are ultrasonic for 1.5-2h and then standing for 22-24h; the temperature of the temperature-controlled vacuum drying is 30-35°C.

[0020] A method for preparing antistatic TPU particles specifically comprises the following steps:

[0021] S1, mixing carbon nanotubes, reduced graphene oxide and N,N-dimethylformamide uniformly and ultrasonicating, adding didodecyl dimethyl ammonium bromide and stirring under nitrogen protection, washing with deionized water, and freeze-drying to obtain a mixture A;

[0022] S2. Control the temperature and dry the polyester thermoplastic polyurethane elastomer, mixed material A, modified silica and modified wood fiber; add the dried polyester thermoplastic polyurethane elastomer, mixed material A, modified silica, modified wood fiber, octyl tributyl phosphonium bis(trifluoromethanesulfonyl)imide salt and melamine into an internal mixer in sequence for melt blending, extrusion and granulation to obtain TPU granule finished products.

[0023] As a preferred technical solution of the present invention, the ultrasonic time in step S1 is 0.5-1h; the stirring time is 22-24h.

[0024] As a preferred technical solution of the present invention, the temperature of the temperature-controlled drying in step S2 is 80-85°C and the time is 5-6h; the internal mixer is first operated at 10-15rpm for 3-4min and then controlled to 50-55rpm for 10-15min, during which the temperature of each zone is 70°C.

[0025] Beneficial effects of the present invention:

[0026] (1) The present invention selects carbon nanotubes and reduced graphene oxide as antistatic fillers to form a conductive network structure in the system, thereby reducing the volume resistivity. At the same time, didodecane dimethyl ammonium bromide is added to modify the antistatic filler so that its surface is connected with an alkyl chain, which hinders the stacking of the antistatic filler so that it is evenly dispersed in the matrix and strengthens the construction of the conductive network. On this basis, octyl tributyl phosphonium bis (trifluoromethanesulfonyl) imide salt is added to produce a certain migration effect in the matrix, thereby compensating for the defects of a part of the conductive network of the antistatic filler. Therefore, the TPU particles prepared in this way have an excellent antistatic effect.

[0027] (2) The present invention further compounds modified silica and modified wood fibers as mechanical fillers on the basis of carbon nanotubes. Compounding the modified mechanical fillers can effectively increase their compatibility with the matrix, so that the carbon nanotubes, modified silica and modified wood fibers can synergistically increase the mechanical properties of the system; on this basis, the present invention further adds melamine containing a rigid triazine ring structure to play a role in bearing stress together with the matrix, so the TPU particles obtained thereby have excellent tensile properties. DETAILED DESCRIPTION

[0028] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] The polyester thermoplastic polyurethane elastomer used in the embodiment of the present invention has the brand name: WHT-1185, which is purchased from Wanhua Chemical Group Co., Ltd.; the carbon nanotubes used have a radial size of nanometers and an axial size of micrometers, CAS number: 308068-56-6, purchased from Shanghai Liantian Materials Technology Co., Ltd.; the reduced graphene oxide used has the number of layers: single layer, item number: R487602, purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.; the modified silica used is nano-silica modified with γ-aminopropyltriethoxysilane, purchased from Xi'an Qiyue Biotechnology Co., Ltd.; the octyltributylphosphonium bis(trifluoromethanesulfonyl)imide salt used has the CAS number: 934215-88-0, purchased from Changsha Binghang New Materials Co., Ltd.; the above will not be repeated in the following.

[0030] Example 1

[0031] An antistatic TPU particle, the TPU particle specifically comprises the following raw materials in parts by weight:

[0032]

[0033] The number of reduced graphene oxide layers: single layer, sheet diameter: 1 μm;

[0034] The preparation method of the modified wood fiber comprises the following steps:

[0035] The wood fiber with a diameter of 10 μm was ultrasonically cleaned in N,N-dimethylformamide for 2 hours, washed with deionized water for 3 times, and dried at 95°C for 10 hours. A 10 mmol / L Tris hydrochloride solution was added to the dried wood fiber for ultrasonic dispersion for 15 minutes, and then dopamine hydrochloride was added. The pH was adjusted to 8.5 with a 0.1 mol / L sodium hydroxide solution. The fiber was ultrasonically cleaned for 2 hours and then allowed to stand for 23 hours. The wood fiber was taken out, washed with deionized water for 3 times, and dried under vacuum at 30°C to obtain modified wood fiber.

[0036] The amount of N,N-dimethylformamide added is just enough to cover the wood fiber; the amount ratio of the dried wood fiber, Tris hydrochloride solution and dopamine hydrochloride is 3.5g:220mL:0.5g;

[0037] A method for preparing antistatic TPU particles specifically comprises the following steps:

[0038] S1. The carbon nanotubes, reduced graphene oxide and N,N-dimethylformamide in the above weight parts are mixed evenly and ultrasonicated for 0.5 h, and didodecyl dimethyl ammonium bromide is added and stirred for 23 h under nitrogen protection, and then washed with deionized water and freeze-dried to obtain a mixture A;

[0039] S2, drying the polyester thermoplastic polyurethane elastomer, the mixture A, the modified silica and the modified wood fiber at 80° C. for 5 h, adding the dried polyester thermoplastic polyurethane elastomer, the mixture A, the modified silica, the modified wood fiber, octyl tributyl phosphonium bis(trifluoromethanesulfonyl)imide salt and melamine to an internal mixer in sequence for melt blending, extrusion and granulation to obtain TPU granule finished products;

[0040] In step S2, the internal mixer is first operated at 10 rpm for 3.5 min and then controlled to operate at 50 rpm for 10 min, during which the temperature in each zone is 170° C.

[0041] Example 2

[0042] An antistatic TPU particle, the TPU particle specifically comprises the following raw materials in parts by weight:

[0043]

[0044] The number of reduced graphene oxide layers: single layer, sheet diameter: 3 μm;

[0045] The preparation method of the modified wood fiber comprises the following steps:

[0046] The wood fiber with a diameter of 8 μm was ultrasonically cleaned in N,N-dimethylformamide for 2 hours, washed with deionized water for 5 times, and dried at 98°C for 12 hours. A 10 mmol / L Tris hydrochloride solution was added to the dried wood fiber for ultrasonic dispersion for 18 minutes, and then dopamine hydrochloride was added. The pH was adjusted to 8.5 with a 0.1 mol / L sodium hydroxide solution. The fiber was ultrasonically cleaned for 1.5 hours and then allowed to stand for 22 hours. The wood fiber was taken out, washed with deionized water for 4 times, and dried under vacuum at 35°C to obtain modified wood fiber.

[0047] The amount of N,N-dimethylformamide added is just enough to cover the wood fiber; the amount ratio of the dried wood fiber, Tris hydrochloride solution and dopamine hydrochloride is 3g:230mL:0.7g;

[0048] A method for preparing antistatic TPU particles specifically comprises the following steps:

[0049] S1. The carbon nanotubes, reduced graphene oxide and N,N-dimethylformamide in the above weight parts are mixed evenly and ultrasonicated for 1 hour, and didodecyl dimethyl ammonium bromide is added and stirred for 22 hours under nitrogen protection, and then washed with deionized water and freeze-dried to obtain a mixture A;

[0050] S2, drying the polyester thermoplastic polyurethane elastomer, the mixture A, the modified silica and the modified wood fiber at 85°C for 5.5h, adding the dried polyester thermoplastic polyurethane elastomer, the mixture A, the modified silica, the modified wood fiber, octyl tributyl phosphonium bis(trifluoromethanesulfonyl)imide salt and melamine to an internal mixer in sequence for melt blending, extrusion and granulation to obtain TPU granule finished products;

[0051] In step S2, the internal mixer is first operated at 10 rpm for 3 min and then controlled to operate at 55 rpm for 13 min, during which the temperature in each zone is 165°C.

[0052] Example 3

[0053] An antistatic TPU particle, the TPU particle specifically comprises the following raw materials in parts by weight:

[0054]

[0055] The number of reduced graphene oxide layers: single layer, sheet diameter: 5 μm;

[0056] The preparation method of the modified wood fiber comprises the following steps:

[0057] The wood fiber with a diameter of 12 μm was ultrasonically cleaned in N,N-dimethylformamide for 2.5 hours, washed with deionized water for 4 times, and dried at 100°C for 11 hours. A 10 mmol / L Tris hydrochloride solution was added to the dried wood fiber for ultrasonic dispersion for 20 minutes, and then dopamine hydrochloride was added. The pH was adjusted to 8.5 with a 0.1 mol / L sodium hydroxide solution. The fiber was ultrasonically cleaned for 2 hours and then allowed to stand for 24 hours. The wood fiber was taken out, washed with deionized water for 5 times, and dried under vacuum at 33°C to obtain modified wood fiber.

[0058] The amount of N,N-dimethylformamide added is just enough to cover the wood fiber; the amount ratio of the dried wood fiber, Tris hydrochloride solution and dopamine hydrochloride is 4g:240mL:0.6g;

[0059] A method for preparing antistatic TPU particles specifically comprises the following steps:

[0060] S1. The carbon nanotubes, reduced graphene oxide and N,N-dimethylformamide in the above weight parts are mixed evenly and ultrasonicated for 1 hour, and didodecyl dimethyl ammonium bromide is added and stirred for 24 hours under nitrogen protection, and then washed with deionized water and freeze-dried to obtain a mixture A;

[0061] S2, drying the polyester thermoplastic polyurethane elastomer, the mixture A, the modified silica and the modified wood fiber at 82.5°C for 6 hours, adding the dried polyester thermoplastic polyurethane elastomer, the mixture A, the modified silica, the modified wood fiber, octyl tributyl phosphonium bis(trifluoromethanesulfonyl)imide salt and melamine to an internal mixer in sequence for melt blending, extrusion and granulation to obtain TPU granule finished products;

[0062] In step S2, the internal mixer is first operated at 15 rpm for 4 min and then controlled to operate at 55 rpm for 15 min, during which the temperature in each zone is 160°C.

[0063] Comparative Example 1

[0064] Compared with Example 3, the difference is that in Comparative Example 1, graphene oxide is used instead of reduced graphene oxide, the graphene oxide has 1 layer and a sheet diameter of 5 μm, which is purchased from Suzhou Carbon Graphene Technology Co., Ltd.; the other operating steps and parameters remain unchanged.

[0065] Comparative Example 2

[0066] Compared with Example 3, the difference is that didodecyl dimethyl ammonium bromide is not added in Comparative Example 2, and the other operating steps and parameters remain unchanged.

[0067] Comparative Example 3

[0068] Compared with Example 3, the difference is that in Comparative Example 3, octyltributylphosphonium bis(trifluoromethanesulfonyl)imide salt is not added, and the other operating steps and parameters remain unchanged.

[0069] Comparative Example 4

[0070] Compared with Example 3, the difference is that in Comparative Example 4, no carbon nanotubes are added, and modified silicon dioxide with half the weight of carbon nanotubes and modified wood fiber with half the weight of carbon nanotubes are used instead, and the other operating steps and parameters remain unchanged.

[0071] Comparative Example 5

[0072] Compared with Example 3, the difference is that in Comparative Example 5, modified silica is not added, and carbon nanotubes with half the weight of modified silica and modified wood fibers with half the weight of modified silica are used instead, and the other operating steps and parameters remain unchanged.

[0073] Comparative Example 6

[0074] Compared with Example 3, the difference is that in Comparative Example 6, no modified wood fiber is added, and carbon nanotubes with half the weight of the modified wood fiber and modified silica with half the weight of the modified wood fiber are used instead, and the other operating steps and parameters remain unchanged.

[0075] Comparative Example 7

[0076] Compared with Example 3, the difference is that dopamine hydrochloride is not added during the preparation of the modified wood fiber in Comparative Example 7, and the other operating steps and parameters remain unchanged.

[0077] Comparative Example 8

[0078] Compared with Example 3, the difference is that in Comparative Example 8, melamine is not added, and the other operating steps and parameters remain unchanged.

[0079] Test Example 1

[0080] According to GB / T 1410-2006, the surface resistivity of the TPU particles prepared in Examples 1-3 and Comparative Examples 1-3 was tested, and the results are shown in Table 1.

[0081] Table 1

[0082]

[0083]

[0084] It can be seen from Table 1 that Examples 1-3 have lower surface resistivity than Comparative Examples 1-3, that is, have good antistatic properties. Therefore, it is obvious that the TPU particles prepared in the present invention have excellent antistatic effects.

[0085] Test Example 2

[0086] According to GB / T 528-1998, the tensile strength (MPa) of the TPU particles prepared in Examples 1-3 and Comparative Examples 4-8 was tested. The results are shown in Table 2.

[0087] Table 2

[0088] Tensile strength / MPa Example 1 53.9 Example 2 53.0 Example 3 54.6 Comparative Example 4 40.8 Comparative Example 5 43.5 Comparative Example 6 46.7 Comparative Example 7 48.6 Comparative Example 8 47.9

[0089] It can be seen from Table 2 that the TPU particles prepared in the present invention have excellent tensile properties.

[0090] In the description of the specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.

[0091] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall all fall within the protection scope of the present invention.

Claims

1. An antistatic TPU particle, characterized in that: The TPU particles specifically include the following raw materials in parts by weight:

2. The antistatic TPU particles according to claim 1, characterized in that: The TPU particles also include N,N-dimethylformamide.

3. The antistatic TPU particles according to claim 2, characterized in that: The N,N-dimethylformamide is 200-300 parts by weight.

4. The antistatic TPU particles according to claim 1, characterized in that The preparation method of the modified wood fiber comprises the following steps: ultrasonically cleaning the wood fiber in N,N-dimethylformamide, washing, and temperature-controlled drying, adding Tris hydrochloride solution to the dried wood fiber for ultrasonic dispersion, then adding dopamine hydrochloride, adjusting pH, ultrasonically dispersing, standing, taking out the wood fiber, washing, and temperature-controlled vacuum drying to obtain the modified wood fiber.

5. The antistatic TPU particles according to claim 4, characterized in that: The wood fiber has a diameter of 8-12 μm.

6. The antistatic TPU particles according to claim 4, characterized in that: The amount of N,N-dimethylformamide added is just enough to cover the wood fiber; the amount ratio of the dried wood fiber, Tris hydrochloride solution and dopamine hydrochloride is 3-4g:220-240mL:0.5-0.7g.

7. The antistatic TPU particles according to claim 4, characterized in that: The ultrasonic cleaning time is 2-2.5h; the washing is done with deionized water for 3-5 times; the temperature of the temperature-controlled drying is 95-100°C and the time is 10-12h; the concentration of the Tris hydrochloride solution is 10mmol / L; the ultrasonic dispersion time is 15-20min; the pH is adjusted to pH=8.5 using 0.1mol / L sodium hydroxide solution; the ultrasonic and standing time is ultrasonic for 1.5-2h and then standing for 22-24h; the temperature of the temperature-controlled vacuum drying is 30-35°C.

8. A method for preparing antistatic TPU particles according to any one of claims 2 to 7, characterized in that: The specific steps include: S1, mixing carbon nanotubes, reduced graphene oxide and N,N-dimethylformamide uniformly and ultrasonicating, adding didodecyl dimethyl ammonium bromide and stirring under nitrogen protection, washing with deionized water, and freeze-drying to obtain a mixture A; S2. Control the temperature and dry the polyester thermoplastic polyurethane elastomer, mixed material A, modified silica and modified wood fiber; add the dried polyester thermoplastic polyurethane elastomer, mixed material A, modified silica, modified wood fiber, octyl tributyl phosphonium bis(trifluoromethanesulfonyl)imide salt and melamine into an internal mixer in sequence for melt blending, extrusion and granulation to obtain TPU granule finished products.

9. The method for preparing antistatic TPU particles according to claim 1, characterized in that: The ultrasonic time in step S1 is 0.5-1h; the stirring time is 22-24h.

10. The method for preparing antistatic TPU particles according to claim 1, characterized in that: The temperature of the temperature-controlled drying in step S2 is 80-85°C for 5-6 hours; the internal mixer is first operated at 10-15 rpm for 3-4 minutes and then controlled at 50-55 rpm for 10-15 minutes, during which the temperature of each zone is 70°C.

Citation Information

Patent Citations

  • Functional graphene / TPU (thermoplastic polyurethane) film as well as preparation method and application thereof

    CN104530686A

  • Polyurethane automobile interior decorating material toughened by wood fiber and preparation method of polyurethane automobile interior decorating material

    CN105331085A

  • Antibacterial antistatic TPU film material and preparation method thereof

    CN109096740A

  • High-transparency TPU film for electronic product and preparation method of high-transparency TPU film

    CN112239595A

  • Anti-static foaming elastomer material and preparation method thereof

    CN116655881A